2017
DOI: 10.1515/mammalia-2016-0096
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of leaves by Carollia perspicillata (Chiroptera, Phyllostomidae): a new dimension of the species’ feeding ecology

Abstract: Relatively little is known about folivory in bats, which is considered an occasional item in the diet of phyllostomids. Here we provide evidence on the consumption of leaves by Carollia perspicillata in northeastern Brazil, through records of its feeding behavior using camera traps, during the monitoring of the Gruta da Janela cave. The analysis of 12 months of monitoring revealed folivory in 7 months. Extra footage (1-min samples) allowed us to confirm C. perspicillata consuming the whole leaf (juices and fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
8
0
2
Order By: Relevance
“…2). Thus, we focus on phyllostomid species, which feature significant differences in overall cranial length [15,31] that we could collect from the wild: Carollia perspicillata, a predominantly frugivorous bat [56,78] with a face near the center of cranial shape morphospace (Fig. 2); Artibeus jamaicensis, a predominantly frugivorous bat [41] with a short and wide face; and Glossophaga soricina, a predominantly nectarivorous and pollenivorous bat [12] with an elongated head and narrow face.…”
Section: Introductionmentioning
confidence: 99%
“…2). Thus, we focus on phyllostomid species, which feature significant differences in overall cranial length [15,31] that we could collect from the wild: Carollia perspicillata, a predominantly frugivorous bat [56,78] with a face near the center of cranial shape morphospace (Fig. 2); Artibeus jamaicensis, a predominantly frugivorous bat [41] with a short and wide face; and Glossophaga soricina, a predominantly nectarivorous and pollenivorous bat [12] with an elongated head and narrow face.…”
Section: Introductionmentioning
confidence: 99%
“…Leaves of E. poeppigiana were the most common and almost the only species recovered intact below the roost of A. lituratus (Table 1). Similar average numbers of intact leaves of E. poeppigiana were brought by both species of bats to their roosting sites (Figure 2) below the roost of Carollia perspicillata in Laranjeiras (Brazil), were completely intact, and the authors suggested that these might have been carried to the cave accidentally by bats (Pereira et al 2017). These authors also showed a picture of an intact composite leaf of Senna georgica (H.S.…”
mentioning
confidence: 81%
“…Folivory has been reported in eight species of phyllostomid bats from the genera Artibeus (Leach 1821), Platyrrhinus (Saussure 1860) and Carollia (Gray 1838) (Greenhall 1957, Van der Pijl 1957, Zortéa and Mendes 1993, Kunz and Ingalls 1994, Kunz and Díaz 1995, Zortéa 1996, Bernard 1997, Esberard et al 1998, Aguiar 2005, Acosta and Aguanta 2006, Novaes and Nobre 2009, Bobrowiec and Cunha 2010, Ruiz-Ramoni et al 2011, Cordero-Schmidt et al 2016, da Rocha et al 2016, Pereira et al 2017. Most observations of leaf consumption document bats chewing small portions of the leaf, extracting the leaf liquids and discarding the remaining fibers (Kunz and Díaz 1995), with the exception of one case [Carollia perspicillata (Linnaeus 1758)] of young leaves which were consumed whole, presumably because they were less fibrous and more digestible (Pereira et al 2017). Folivory is seen as a strategy that might provide vitamins and micronutrients not always available in fruits, and/or proteins that are particularly important during pregnancy and lactation but usually scarce in fruits.…”
mentioning
confidence: 99%
“…Geralmente, utiliza ambientes florestais, eventualmente campos abertos. Consome principalmente frutos, mas também insetos, néctar, pólen e folhas (Pereira et al, 2017). No Pantanal, consome principalmente frutos de Piper tuberculatum (Piperaceae), pólen e néctar de Bauhinia ungulata (Fabaceae), além de lepidópteros (Munin et al, 2012).…”
Section: Carollia Perspicillata (Linnaeus 1758) (Figura 66)unclassified